PTU-054 Transjugular intrahepatic portosystemic shunts following liver transplantation can be associated with a good prognosis: a single centre experience. (28th May 2012) - Hogan, B; Thorburn, D; Sharma, D; Davidson, B; O'Beirne, J P; Burroughs, A K; Yu, D; Patch, D W
Abstract : Introduction: Transjugular intrahepatic portosystemic shunt (TIPS) is indicated in the management of portal vein thrombosis or stenosis, portal hypertension and for veno-occlusive disease in post-liver transplant (LT) patients. Previous series have reported 1-year mortality rates of 14%–67%. A MELD score >15 at the time of insertion may indicate a poor long term prognosis. We aimed to evaluate the safety of TIPS after LT at a UK tertiary referral centre. Methods: We retrospectively analysed data from the Royal Free Hospital TIPS database between 1st January 1991 and the 31st January 2011. All patients who had undergone TIPS following LT were included. Results: During the period studied 629 patients received a TIPS. In the same period 1192 liver transplant operations were performed. 10 TIPS were inserted into patients following LT for recurrent cirrhosis with refractory ascites (4), veno-occlusive disease (3) and portal vein thrombosis (3). The original indications for transplantation were PSC (3), PBC (3), Hepatitis C (1), Autoimmune (1), Primary Oxalosis (1) and Acute Liver Failure (1). We noted a median survival of 38 months. Survival at 1 and 5 years was 100% and 60% respectively. The median MELD at the time of TIPS insertion was 12 (range 7–19). No correlation between the MELD score at the time of TIPS insertion and survival was demonstrated (p=0.62). Conclusion: These results suggest that TIPS can be performed safely after LT and that survival rates better than those previously reported can be achieved. We suggest TIPS should be used in carefully selected candidates following LT as a definitive treatment for patients not suitable for re-transplant or as a bridge to re-transplantation. The alternative of re-transplantation should always be considered prior to TIPS insertion where indicated. Competing interests: None declared. References: 1. Saad WEA, et al. Transjugular intrahepatic portosystemic shunts in liver transplant recipients for management of refractory ascites: clinical outcome. J Vasc Interv Radiol 2010;21 :218–23. 2. Kim JJ, et al. Transjugular intrahepatic portosystemic shunts in liver transplant recipients. Liver Int 2008;28 :240–8. 3. Feyssa E, et al. MELD score less than 15 predicts prolonged survival after transjugular intrahepatic portosystemic shunt for refractory ascites after liver transplantation. Transplantation 2011;91 :786–92.